(untitled) (Canadian Medical Education Journal, 2026)
Implication statement Since 2012, the Royal College of Physicians and Surgeons of Canada (RCPSC) has transitioned residency programs from time-based to competency-based medical education (CBME). Consistent with best practices in CBME implementation, the Structured Interview Matrix (SIM) provides an efficient, inclusive mechanism to solicit diverse perspectives. By promoting broad participation and shared ownership, SIM enhances the relevance, validity, and sustainability of curricular change, and can be adapted for broader curriculum co-design. To our knowledge, SIM has not been used in medical education before.